KNOWLEDGE MANAGEMENT, TECHNOLOGY, STRATEGY, AND ENVIRONMENT IN HALAL FOOD INDUSTRY GREEN SUPPLY CHAIN AND LOGISTICS MANAGEMENT PERFORMANCE (Journal of Technology and Operations Management, 2023)
The green supply chain and logistics management (GSCLM) in the halal food industry from upstream to downstream is to ensure systems integrity as the performance output. The issues in the GSCLM for the halal food industry are mainly costs, quality, non-segregation, and cross-contamination of halal-haram goods in supply chain processes. Therefore, the paper reveals the knowledge of the key factors for GSCLM in the context of the halal food industry. The research is hypothetically deducted from a transactional cost economic (TCE) and used a quantitative approach. A survey questionnaire was distributed to the halal food industry managers across the country. The key findings from PLS-SEM analysis indicated that technology, strategy, and environment affected the GSCLM through knowledge management. Nevertheless, technology had a small effect on GSCLM. The limitations of the research as it was conducted in the halal food industry, hence the generalizability of our findings is contingent on the validation of the findings with the non-specific halal certification industry. Practical implications are realized in which the industry could enhance the knowledge management in GSCLM effectively. Government should also support the industry with new policies and regulations that could fulfill the halal market demand. Future research may apply other theories to be tested in the context of GSCLM in other non-specific halal certification industries. The paper provides a new model of GSCLM in the halal food industry. Specifically, it applies TCE in GSCLM which demonstrates how knowledge management can affect the GSCLM performance.